Problems of Russian Innovative Renewal in Conditions of Financial and Economic Crisis - Viktor Petrovich Kirilenko; Roman Vladimirovich Dronov (Управленческое консультирование, 2018)
The theme selection of a subject of this work is caused by the fact that in the conditions of proceeding financial and economic crisis, many economic entities of the Russian economy having passed a privatization stage, and then and capitalizations of the possession have faced a problem of lack of means for the further innovative updating demanding big investment investments. Creating favorable conditions for the implementation of innovation is one of the most important tasks of the public policy developed countries. Accordingly, stimulation of innovation acts as a mechanism for implementing the strategic objectives of government policy in general and its innovative component in particular.